2023
DOI: 10.3390/jcdd10050197
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Trimethylamine N-Oxide and Coronary Microcirculatory Dysfunction on Outcomes following ST-Elevation Myocardial Infarction

Abstract: Introduction: Persistent coronary microcirculatory dysfunction (CMD) and elevated trimethylamine N-oxide (TMAO) levels after ST-elevation myocardial infarction (STEMI) may drive negative structural and electrical cardiac remodeling, resulting in new-onset atrial fibrillation (AF) and a decrease in left ventricular ejection fraction (LVEF). Aims: TMAO and CMD are investigated as potential predictors of new-onset AF and left ventricular remodeling following STEMI. Methods: This prospective study included STEMI p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Conversely, elevated plasma levels of TMAO independently correlated with a high risk of plaque rupture in STEMI patients ( 245 ). Additionally, studies have consistently indicated that high TMAO levels are positively associated with MACEs, atrial fibrillation, and coronary atherosclerotic burden ( 209 , 213 , 246 248 ). TMAO holds promise as a valuable biomarker for predicting poor prognosis and improving risk assessment and management in MI patients.…”
Section: Single-omics Approachesmentioning
confidence: 99%
“…Conversely, elevated plasma levels of TMAO independently correlated with a high risk of plaque rupture in STEMI patients ( 245 ). Additionally, studies have consistently indicated that high TMAO levels are positively associated with MACEs, atrial fibrillation, and coronary atherosclerotic burden ( 209 , 213 , 246 248 ). TMAO holds promise as a valuable biomarker for predicting poor prognosis and improving risk assessment and management in MI patients.…”
Section: Single-omics Approachesmentioning
confidence: 99%
“…The link between abnormal CFR, IMR, and unfavorable clinical outcomes in patients with STEMI has been repeatedly demonstrated. 8 , 9 …”
mentioning
confidence: 99%